Occupational Therapy and Primary Care: Updates and Trends - Halle, Ashley D. (Am J Occup Ther, 2018)
As our health care system continues to change, so do the opportunities for occupational therapy. This article provides an update to a 2012 Health Policy Perspectives on this topic. We identify new initiatives and opportunities in primary care, explore common challenges to integrating occupational therapy in primary care environments, and highlight international works that can support our efforts. We conclude by discussing next steps for occupational therapy practitioners in order to continue to progress our efforts in primary care.